A novel tool for continuous fracture aftercare – Clinical feasibility and first results of a new telemetric gait analysis insole. Issue 2 (February 2016) - Braun, Benedikt J.; Bushuven, Eva; Hell, Rebecca; Veith, Nils T.; Buschbaum, Jan; Holstein, Joerg H.; Pohlemann, Tim
Abstract: Weight bearing after lower extremity fractures still remains a highly controversial issue. Even in ankle fractures, the most common lower extremity injury no standard aftercare protocol has been established. Average non weight bearing times range from 0 to 7 weeks, with standardised, radiological healing controls at fixed time intervals. Recent literature calls for patient-adapted aftercare protocols based on individual fracture and load scenarios. We show the clinical feasibility and first results of a new, insole embedded gait analysis tool for continuous monitoring of gait, load and activity. Ten patients were monitored with a new, independent gait analysis insole for up to 3 months postoperatively. Strict 20 kg partial weight bearing was ordered for 6 weeks. Overall activity, load spectrum, ground reaction forces, clinical scoring and general health data were recorded and correlated. Statistical analysis with power analysis, t -test and Spearman correlation was performed. Only one patient completely adhered to the set weight bearing limit. Average time in minutes over the limit was 374 min. Based on the parameters load, activity, gait time over 20 kg weight bearing and maximum ground reaction force high and low performers were defined after 3 weeks. Significant difference in time to painless full weight bearing between high and low performers was shown. Correlation analysis revealed a significant correlation between weight bearing and clinical scoring as well as pain (American Orthopaedic Foot and Ankle Society (AOFAS) Score r s  = 0.74; Olerud–Molander Score r s  = 0.93; VAS pain r s  = −0.95). Early, continuous gait analysis is able to define aftercare performers with significant differences in time to full painless weight bearing where clinical or radiographic controls could not. Patient compliance to standardised weight bearing limits and protocols is low. Highly individual rehabilitation patterns were seen in all patients. Aftercare protocols should be adjusted to real-time patient conditions, rather than fixed intervals and limits. With a real-time measuring device high performers could be identified and influenced towards optimal healing conditions early, while low performers are recognised and missing healing influences could be corrected according to patient condition.